2015
DOI: 10.1128/iai.00787-15
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies Variations in Bordetella Catecholamine Receptor Gene Regulation and Function

Abstract: Bordetella bronchiseptica can use catecholamines to obtain iron from transferrin and lactoferrin via uptake pathways involving the BfrA, BfrD, and BfrE outer membrane receptor proteins, and although Bordetella pertussis has the bfrD and bfrE genes, the role of these genes in iron uptake has not been demonstrated. In this study, the bfrD and bfrE genes of B. pertussis were shown to be functional in B. bronchiseptica, but neither B. bronchiseptica bfrD nor bfrE imparted catecholamine utilization to B. pertussis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…This analysis revealed a network with connections to many other factors, some of which are known to be involved in complex interactions with the host. In addition to T3SS, this analysis indicated that btrS is connected with other genes encoding known virulence regulators such as hfq 39,40 and sigE (RpoE) 41,42 , as well as iron and heme sensors 30,43,44 , transporters, and other membrane proteins. Roles for some of these factors in immunomodulation and/or pathogenesis of several organisms has been reported 45–59 .…”
Section: Resultsmentioning
confidence: 93%
“…This analysis revealed a network with connections to many other factors, some of which are known to be involved in complex interactions with the host. In addition to T3SS, this analysis indicated that btrS is connected with other genes encoding known virulence regulators such as hfq 39,40 and sigE (RpoE) 41,42 , as well as iron and heme sensors 30,43,44 , transporters, and other membrane proteins. Roles for some of these factors in immunomodulation and/or pathogenesis of several organisms has been reported 45–59 .…”
Section: Resultsmentioning
confidence: 93%
“…It is well-established that Bordetella spp. sense details of the local host environment [ 65 , 92 , 93 , 94 , 95 ] and carefully and coordinately regulate multiple mechanisms to modulate host immune responses, suppressing the generation of robust immunity [ 55 , 92 , 96 ]. The type 3 and type 6 secretion systems [ 97 , 98 ], adenylate cyclase toxin [ 99 , 100 , 101 ], pertussis toxin [ 102 , 103 ], and other immunomodulators can affect immune cells in vitro and in vivo, and disrupting their carefully choreographed expression can lead to much more robust adaptive immunity [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Armstrong et al hypothesized that Bordetella spp. may be exposed to nutritionally relevant catecholamine concentrations in the local microenvironment during infection, either on the mucosal surface via serum exudation or through interaction with immune cells [34]. Noradrenaline has been shown to have a strong iron shuttling activity, allowing Bordetella spp.…”
Section: Bordetella Respond To Host Environmentmentioning
confidence: 99%
“…In the absence of siderophores, catecholamines would remove the iron from transferrin and lactoferrin to directly bind it to B. bronchiseptica [13]. The mechanisms by which these neuroendocrine catecholamines; including epinephrine, norepinephrine, and dopamine, function is by increasing transcription of bfeA (outer membrane protein) of B. bronchiseptica, which is involved in transporting ferric catechol [13,34].…”
Section: Bordetella Respond To Host Environmentmentioning
confidence: 99%